STRATEGI VALUATION MODEL: PENGAMBILAN KEPUTUSAN INVESTASI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hasa Nurrohim KP; Sri Dwi Ari Ambarwati (Jurnal Keuangan dan Perbankan, 2008)
This research was based upon Riahi-Belkaoui Picur (2001) and Richard G Baker(1999) result which supposed there was relation between IOS with dividend and retained earningpolicy. Purpose of this research was to know empirically impact of valuation model strategy toinvestment decision making on manufacturing company. Using data of manufacturing companieswas listed during 2000-2005 in Indonesia Stock Exchange and analyzed with multiple regression.The results found were: 1). There was no effect between stock price with dividend on companiesand High IOS (Investment Opportunity Sets) although Low IOS. 2). There was significantlypositive effect between stock price with retained earning on companies and High IOS (InvestmentOpportunity Sets).